2018
DOI: 10.14302/issn.2638-4469.japb-18-2423
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants and their Traditional Uses

Abstract: It is estimated that there is the number of between 750,000 and 1,000,000 plant species on the world. The 500,000 of them have been identified and named. Around 2000 new flowering plant species are identified and named in each year. The number of plants which have been used for treatment since ancient times shows a steady increase. According to a report released by the World Health Organization (WHO), the number of plants used for treatment is estimated to be around 20,000. The studies on medicinal plants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…According to WHO, the number of plants used for treatment is estimated to be 20,000 named as medicinal plants. The studies on medicinal plants and active substances derived from these have increased the interest in these plants recent years [ 7 ]. There are about 45 plant families with 4000 genus that contain these medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO, the number of plants used for treatment is estimated to be 20,000 named as medicinal plants. The studies on medicinal plants and active substances derived from these have increased the interest in these plants recent years [ 7 ]. There are about 45 plant families with 4000 genus that contain these medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Gundelia tournefortii (GT), a member of the Asteraceae family, is an artichoke-like medicinal plant that grows in countries such as Iran, Cyprus, Egypt, Jordan, Turkey, Azerbaijan, and Turkmenistan [25,26]. All parts of GT have been used both as a food source and as a medicinal plant since ancient times [27].…”
Section: Introductionmentioning
confidence: 99%
“…All parts of GT have been used both as a food source and as a medicinal plant since ancient times [27]. It has been reported that it was used in the treatment of many diseases in traditional folk medicine [25][26][27]. The size of AuNPs is smaller compared to that of nanoparticles synthesized from metals such as copper, titanium, zinc, iron, and silver.…”
Section: Introductionmentioning
confidence: 99%
“…For the large population of the world, nowadays medicinal plants present a dominant role in the healthcare system and financial aids. In diversified industries and development of new drug discovery, the contribution of plants and especially medicinal plants is remarkable as their roles have proved in coping with a number of deadly diseases such as cancer, hepatitis, and AIDS etc, Hamburger and Hostettmann, 1991; Harrison, 1998; Ahmad Dar et al, 2017; Keskin, 2018; Dehdari and Hajimehdipoor, 2018. Following the latest scientific estimations, a very large spectrum of plant species including new ones is characterized each year.…”
Section: Introductionmentioning
confidence: 99%